Peningkatan Kualitas Usaha Manisan Desa Bati Bati Kabupaten Tanah Laut - Daniel Itta; Dewi Fitriyanti; Susilawati Susilawati; Raudatul Jannah (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Along with the development of tourism in Tanah Laut Regency, some Bati Bati residents have opened a business selling candied fruit. The average income of candied fruit traders ranges from Rp. 500,000 to 1,000,000 per month. Most of these small and medium enterprises are their main income and some are side activities other than as laundry workers and housewives. Candied fruit trading business that is engaged in by Mandiri UKM mothers. established in early 2016 and growing until now. However, the business conditions of this women's group require attention and touch from other parties in order for significant business development to occur. Meanwhile, based on observations so far, candied fruit is still underdeveloped, including 1) the types / types are less varied, 2) packaging / presentation is relatively simple 3) Quality still needs to be improved because candied fruit still uses saccharin so it tastes bitter and 4) marketing has not so wide. These problems need to be solved, namely (a) Training on making candied fruit with various flavors (original, spicy) that is healthy and durable (b) Training on packaging that attracts consumers and makes product brands that are made so that they have an identity at the same time. as a means of promotion (c) Training on standardization of healthy candied fruit and product idea exploration (d) Assistance in market expansion and training in household financial management and business bookkeeping (cash flow).